Manipulating the assembly of the CNC/RGO composite film for superior electromagnetic interference shielding properties. Issue 47 (26th November 2021) - Jin, Kexia; Xing, Jianxiong; Liu, Xinge; Jiang, Zehui; Yang, Shumin; Yang, Xuan; Ma, Jianfeng
Abstract : Manipulating the assembly of CNC/RGO composite films revealed that the CNC with lower diameter leads to a lower porosity, denser structure, and more uniform distribution in the composites, and therefore a higher electrical conductivity and SE. Abstract : To achieve high mechanical strength electromagnetic interference (EMI) shielding materials for practical application, cellulose nanocrystals (CNC), as a reinforcing and dispersing agent, are intercalated into reduced graphene oxide (RGO) layers, forming an ultrathin, robust, flexible, and hydrophobic CNC/RGO film with a highly ordered nacre-like layered structure via a self-assembly process. The layered structure significantly shortens the reduction time and improves the mechanical strength and shielding effectiveness (SE) of the resultant CNC/RGO composite film. The controlled preparation of CNC with different aspect ratios is realized by using separated bamboo fiber and parenchyma. The CNC of the fiber with a higher aspect ratio and lower diameter results in a lower porosity, denser structure, and more uniform distribution in the composites, and therefore a higher electrical conductivity and SE. The highest SE (39.1 dB) and specific SE (11 367 dB cm 2 g −1 ) with a high tensile strength (179 MPa) and water contact angle (106°) of the CNC/RGO film are obtained at 10 wt% CNC loading with a film thickness of 12 μm. The maximum tensile strength of the composite film reaches 227 MPa with 30–50% CNC. The ultrathin high-performance CNC/RGO film shows significant potential as an EMI shielding material in the aerospace and flexible electronics fields.